Parental Involvement in Schooling: Perceptions of African American Parents and Guardians - Martin, Ruthea G. (My University, 2017)
Parental involvement is a crucial factor in the success of students, but research shows differing perceptions on the definition of parent involvement (Wright, 2009). The purpose of this study was to understand the perceptions of African American parents regarding their role in their child's academic success, the nature of their involvement in schools, and the perceived impact of that involvement in their child’s educational future. Twenty African American parents/guardians were interviewed for this study. All participants attended the same Baptist church in one southern city, were over the age of 18, and had at least one child presently attending elementary school. A basic qualitative research design was used for the study and semi-structured, individual interviews with each of the 20 participants provided the data for this study. Viewing the results from Epstein’s six types of parent involvement, the participants in this study were actively involved in five types, but none of them were involved in the “decision-making” category discussed by Epstein. Using Yosso’s (2002) cultural wealth lens to understand the data provided a very different story. It is clear that African American families employ a wealth of communal resources to ensure the academic success of their children. These resources may not be considered when schools talk about the parental involvement of African American parents, yet the wealth of resources in the African American community could provide schools with a critical bridge to increase the academic success of African American students, if school administrators were willing to cross the bridge into the community rather than asking parents to continually cross the bridge and come to school for events and at times that are conducive to schools.
Chapter I: INTRODUCTION..1 | Statement of Problem..5 | Purpose of the Study...6 | Significance of the Study 6 | Conceptual Framework.......7 | Research Design..9 | Procedure.9 | Limitations..10 | Definition of Terms.10 | Organization of the Study 12 | Chapter II: LITERATURE REVIEW..13 | Models of Parent Involvement.........15 | Benefits of Parental Involvement and Student Success...19 | Barriers to Parental Involvement.20 | African American Parental Involvement.21 | Home-School Connections...23 | Policies and Laws That Support Parental Involvement 25 | Parenting Styles.27 | Summary ...29 | Chapter III: METHODOLOGY.....30 | Research Design.30 | Research Questions....30 | Setting 31 | Participants....31 | Data Collection..32 | Interview Procedures.32 | Data Processing and Analysis ..34 | Trustworthiness.34 | Summary 37 | Chapter IV: RESULTS..38 | Brief Profile of Participants...39 | Results 46 | Summary 60 | Chapter V: DISCUSSION & RECOMMENDATION..61 | Discussion of Research Finding.62 | Recommendations..68 | Conclusion.70 | REFERENCES..72 | APPENDICES...95 | Appendix A: Institutional Review Board Approval......95 | Appendix B: Permission from Church..97 | Appendix C: Consent Script..99 | Appendix D: Interview Protocol..101 |
Keywords: Education--Parent participation; African Americans; African Americans--Education--Southern States; Schools